Impact of Intermittent Fasting on Lipid Profile–A Quasi-Randomized Clinical Trial - Ahmed, Naseer; Farooq, Javeria; Siddiqi, Hasan Salman; Meo, Sultan Ayoub; Kulsoom, Bibi; Laghari, Abid H.; Jamshed, Humaira; Pasha, Farooq (Frontiers in Nutrition, 2021)
Background: Sub-optimal HDL is a prognostic marker of cardiovascular disease. South Asia has a high prevalence of sub-optimal HDL compared to other parts of the world. Intermittent fasting (IF) is a type of energy restriction which may improve serum HDL and other lipids thereby reducing the risk of cardiovascular diseases. Objective: The aim of the study was to evaluate the effect of IF on lipid profile and HDL-cholesterol in a sample of South Asian adults. Methods: A 6-week quasi-experimental (non-randomized) clinical trial was conducted on participants with low HDL (< 40 mg/dl for men and < 50 mg/dl for women). Participants of the control group were recommended not to change their diet. The intervention group was recommended to fast for ~12 h during day time, three times per week for 6 weeks. Pulse rate, blood pressure, body weight, waist circumference, serum lipid profile, and blood glucose levels were measured at baseline and after 6 weeks. Result: A total of 40 participants were enrolled in the study (N = 20 in each group), while 35 (20 control and 15 intervention) completed the trial and were included in data analysis of the study. Body measurements, including body weight, BMI and waist circumference, showed significant interaction effects (p's < 0.001), indicating that there were larger reductions in the IF group than in the control group. Significant interaction effects were also observed for total (p = 0.033), HDL (p = 0.0001), and LDL cholesterol (p = 0.010) with larger improvements in the IF group. Conclusion: This study suggests that intermittent fasting may protect cardiovascular health by improving the lipid profile and raising the sub-optimal HDL. Intermittent fasting may be adopted as a lifestyle intervention for the prevention, management and treatment of cardiovascular disorders. Clinical Trial Registration: NCT03805776, registered on January 16, 2019, https://clinicaltrials.gov/ct2/show/NCT03805776